Structural Study of Europium Doped Gadolinium Polyphosphates LiGd(PO3)4 and Its Effect on Their Spectroscopic, Thermal, Magnetic, and Optical Properties - Saoussen Hammami; Nassira Chniba Boudjada; Adel Megriche (International Journal of Analytical Chemistry, 2018)
Alkali metal-rare earth polyphosphates LiGd(1-x)Eux(PO3)4 (LGP:Eu3+) (where x= 0, 0.02 and 0.04) were synthesized by solid-state reaction. The Rietveld refinement showed the following cell parameters: I 2/a space group, a=9.635(3) Å, b=7.035(3) Å, c=13.191(3) Å, β=90.082°, V= 894.214Å3, and Z=4. The similarity between RF=4.21% and RB=4.31% indicated that the realized refinement is reliable. The crystal structure consists of infinite zig-zag chains of PO43- tetrahedra, linked by bridging oxygen. The acyclic structure of polyphosphates is confirmed by infrared and Raman (IR) spectroscopies. A good thermal stability up to 940°C and paramagnetic behavior of these compounds were also proved by thermal analyses and magnetic susceptibility measurements, respectively. Excitation spectra revealed the charge transfer phenomenon between O2- and Eu3+ (CTB), the energy transfer from Gd3+ to Eu3+, and the intrinsic 4f-4f transitions of Eu3+ where the electronic transitions were also identified. Moreover, LGP:Eu3+ can emit intense reddish orange light under excitation at 394 nm. The strongest tow at 578 and 601 nm can be attributed to the transitions from excited state 5D0 to ground states 7F1 and 7F2, respectively.